Without delay: Getting Britain's railways moving - Richard Wellings (Institute of Economic Affairs (IEA), 2016)
The renationalisation of rail infrastructure has not been a success. Network Rail has been plagued by crisis after crisis, with major projects hit by delays, mismanagement and large cost overruns. Its problems echo those suffered by the inefficient nationalised industries of the post-war period. Rail subsidies remain high, with the industry costing taxpayers 5 billion in 2014/15. The railways had been returned to the private sector in the mid-1990s, at the tail end of the privatisation programme. However, unlike the light-touch approach of the 19th century, the sector was subject to strict regulation. A complex artificial structure was imposed on the industry, which separated track and train. Much of the network was subject to price controls. Despite severe regulatory constraints, private train operators were able to bring entrepreneurship and innovation to the sector, including improved marketing and the introduction of very low-cost, off-peak fares. Many of the common criticisms of the post-privatisation industry are misplaced. The sector has however remained heavily dependent on taxpayer funding. The level of financial support from government has increased significantly compared with the British Rail years, yet there has been no step change in outcomes according to several key measures. In terms of cost-effectiveness, the sector's performance has been relatively poor. The rail industry is a good example of how political interference can prevent privatisation from delivering the expected benefits. A successful privatisation model would wean the industry off state support and allow its structure to evolve to more cost-effective organisational forms through mergers and demergers. There is strong evidence that a liberalised railway would exhibit a far higher degree of vertical integration than the current state-imposed model. Private railways should be free to cut costs by closing loss-making lines and services, to introduce "super-peak" fares to tackle overcrowding, to offer cut-price "economy class" options such as standing-only carriages, and to determine an appropriate level of safety expenditure.
Keywords: R40; R41; R42; R48; R49; L26; L51; L53; H11; R40; R41; R42; R48; R49; L26; L51; L53; H11; 330; Railways; nationalization; impact analysis; Great Britain; Schienenstrecke; Verstaatlichung; Wirkungsanalyse; Großbritannien